Left Main Coronary Artery Hypoplasia in Elderly - Selma Kenar Tiryakioglu; Hakan Ozkan; Hakan Bahadir; Osman Tiryakioglu (Case Reports in Cardiology)
Congenital anomalies of the coronary artery causing coronary occlusive disease may be of many different types. A 67-year-old woman with no coronary risk factors was referred for coronary angiography with few months’ history of angina. The patient underwent coronary angiography due to ischemic cardiac symptoms with nondiagnostic exercising test. In coronary angiography, the left main coronary artery was arising from normal anatomical position; however, left anterior descending artery and circumflex artery were hypoplastic. The treatment of patient was discussed in cardiology-cardiovascular surgery council and coronary surgery was found inappropriate due to the hypoplasia of the left coronary system entirely.